O fantasma no castelo do materialismo: uma história do inconsciente Freudiano - Pinheiro, Heráclito Aragão (2009)
This research has the goal of understanding the path of Freud in his elaboration of the notion of unconscious, to realize the ways by which he got to this crucial notion to the foundation of the psychoanalytical knowing. To reach this goal I decided to deal with the models and references of Freud. The principal results were that the models which had more weight in the development of his idea of unconscious were his clinical work with the hysterics, as well as his divergence with the conventional ideas about this affection, his contact with the hypnosis and the interlocution he established with Charcot, Breuer and Fliess. And the principal references were the agnosticism and the physicalism,in relation to what it concerns the form by which he finally distanced himself.